(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The study of orthopoxviruses was steadfastly pursued until the complete disappearance of the variola virus in the 1980s. However, after the 1980s, research on orthopoxviruses slowed down due to their beautiful relevance. In recent years, in connection with the detection of cowpox and monkeypox viruses, not only in animal populations, but also among humans, the study of orthopoxviruses has become more relevant. It is known from earlier studies that some smallpox vaccines have been successfully used to eradicate smallpox, although in most cases the safety of the vaccines has so far been of concern to many virologists. The main reason was that the vaccine was made from animal tissues and many virologists decided to use cell cultures when cultivating viruses. However, to date, the solution to this problem is still open. In this regard, this article presents the results of determining some of the cultural properties of collection strains of orthopoxviruses. As a result of the studies, it was found that vaccinia viruses (VAV) and cowpox (VOK) reproduce freely in the cells of the kidney of the lamb (LA) and in the cells of the kidney of the African green monkey (Vero). At the same time, the cytopathic effect (CPE) of the virus on the cell monolayer occurred quickly, and the period of virus cultivation was reduced from 120 h to 24 h, while the biological activity remained unchanged and amounted to 5.100.10 lgTCID50/cm3 for the WOK strain, for the WOV strain 5.15± 0.10 lgTCID50/cm3 for the WOK strain, for the WOV strain 5.15± 0.11 lgTCID50/cm3. Sequential passaging of viruses in these culture systems did not lead to a significant change in the biological activity of the obtained virus-containing material. The results of these studies are primary incomplete data on the cultural properties of these strains of the virus.